Pengaruh Edukasi melalui Leaflet Terhadap Pengetahuan Ibu Rumah Tangga Tentang Kanker Payudara di RW 14 Kelurahan Kedung Halang Kecamatan Bogor Utara Kota Bogor (Jurnal Kesehatan Siliwangi, 2021)
World Health Organization (WHO) found that there were 65.858 breast cancer cases in Indonesia in 2020 alone. 65,8% breast cancer case group in Dr. Moewardi Hospital had poor breast cancer-related preventive habits. The research was conducted to study on the influence of education through leaflet towards housewife’s knowledge about breast cancer in RW 14 Kedung Halang Sub-District, Northern Bogor District, Bogor City. This study used one group pre-test post-test design. Research population consisted of 150 housewives while 48 were selected as samples using purposive sampling. Univariate analysis conducted using mean formula and bivariate through Wilcoxon. The research showed that the average pre-test score acquired by samples was 56,8 points. However, after intervention, the average score increased by 27,08 points, resulted in 83,54 points average score of post-test. This study proved that education through leaflet towards housewife’s knowledge about breast cancer had significant effect with p value= 0,000 (p ≤ 0,05). Education through leaflet was proven influential towards housewife’s knowledge about breast cancer in RW 14 Kedung Halang Sub-District Northern Bogor District Bogor City. This study can be used by the public as a source of information about breast cancer.